Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1128/jb.06245-11
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Bizionia argentinensis, Isolated from Antarctic Surface Water

Abstract: A psychrotolerant marine bacterial strain, designated JUB59 T , was isolated from Antarctic surface seawater and classified as a new species of the genus Bizionia. Here, we present the first draft genome sequence for this genus, which suggests interesting features such as UV resistance, hydrolytic exoenzymes, and nitrogen metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Although strains of Bizionia from Antarctic Oceans show amidase enzyme activity against a relatively broad range of substrates (Bercovich et al, 2008), strain BB3 (isolated in the present study) showed only a arylamidase activity. A previous study shows that the genome of B. argentinensis JUB59 T contains 24 putative extracellular peptidase genes (Lanzarotti et al, 2011); however, no information is available regarding the extracellular enzyme activity of other Antarctic Bizionia spp. Strains of Proteobacteria showed extracellular enzyme activity against a limited range of test substrates.…”
Section: Flavobacteriamentioning
confidence: 99%
“…Although strains of Bizionia from Antarctic Oceans show amidase enzyme activity against a relatively broad range of substrates (Bercovich et al, 2008), strain BB3 (isolated in the present study) showed only a arylamidase activity. A previous study shows that the genome of B. argentinensis JUB59 T contains 24 putative extracellular peptidase genes (Lanzarotti et al, 2011); however, no information is available regarding the extracellular enzyme activity of other Antarctic Bizionia spp. Strains of Proteobacteria showed extracellular enzyme activity against a limited range of test substrates.…”
Section: Flavobacteriamentioning
confidence: 99%
“…The genome of B. argentinensis was recently decoded and has been deposited at the DDBJ/EMBL/GenBank under the accession code AFXZ00000000. This genome constitutes a relevant source for the discovery of new proteins showing biological activity in extreme conditions of low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have been conducted to evaluate the effect of UV radiation on bacteria isolated from the water column of Potter autochthonous bacterial consortia for on-site bioremediation of hydrocarbon-contaminated soils Vá zquez et al 2009;Ruberto et al 2010), to detect the presence and diversity of naphthalene dioxygenase genes in soils (Flocco et al 2009) and to screen for bacterial extracellular proteases for their use in the cleaning and food industries (Vá zquez et al 2004;Vá zquez et al 2005;Vá zquez et al 2008). A bacterial strain isolated from surface marine water of Potter Cove was described as a new species, Bizionia argentinensis (Bercovich et al 2008), and its complete genome has been sequenced and is being thoroughly studied (Lanzarotti et al 2011). This research has proven the ecological and biotechnological relevance of the culturable fraction of Potter Cove's bacterial community.…”
mentioning
confidence: 99%